Pengaruh Kualitas dan Harga Terhadap Keputusan Pembelian Produk: Studi Kasus Toko Usaha Bersama Surabaya: Effect of Quality and Price on Product Purchasing Decisions: Case Study of Business Stores Bersama Surabaya - Danitra, Revo Ramadhan Putra (Universitas Negeri Surabaya, 2024)
Grocery stores are an important part of everyday life. Some food shops still survive and start to innovate. Research methods that undergo changes in food shops decreases due to minimarkets and supermarkets. It is very important to remember that consumer preferences on quality and prices may vary. Some consumers may only focus on quality without progressing prices, while others may be very sensitive to prices. This difference can be influenced by factors such as personal income and individual preferences. Quality and price factors are interrelated and have a significant effect on product purchasing decisions in a joint business store. Marketing uses an effective strategy needed to maintain a balance between quality products and competitive prices to meet the various needs and expectations of consumers. By understanding how much influence these two factors on purchasing decisions. Keywords: shop, quality, price, purchase